Comparing individual and group intervention for psychological adjustment in people with multiple sclerosis: a feasibility randomised controlled trial. (December 2016) - das Nair, Roshan; Kontou, Eirini; Smale, Kathryn; Barker, Alex; Lincoln, Nadina B
Objective: To modify a published group intervention for adjustment to multiple sclerosis (MS) to suit an individual format, and to assess the feasibility of a randomised controlled trial (RCT) to compare individual and group intervention for people with multiple sclerosis and low mood. Design: Feasibility randomised controlled trial. Setting: Participants were recruited through healthcare professionals at a hospital-based multiple sclerosis service and the MS Society. Subjects: People with multiple sclerosis. Interventions: Adjustment to multiple sclerosis in individual or group delivery format. Main measures: Participants completed mood and quality of life assessments at baseline and at four-month follow-up. Measures of feasibility included: recruitment rate, acceptability of randomisation and the intervention (content and format), and whether the intervention could be adapted for individual delivery. Participants were screened for inclusion using the General Health Questionnaire-12 and Hospital Anxiety and Depression Scale, and were randomly allocated to receive either individual or group intervention, with the same content. Results: Twenty-one participants were recruited (mean age 48.5 years, SD 10.5) and were randomly allocated to individual ( n =11) or group ( n =10) intervention. Of those offered individual treatment, nine (82%) completed all six sessions. Of those allocated to group intervention, two (20%) attended all six sessions and three (30%) attended five sessions. There were no statistically significant differences between the groups on the outcome measures of mood and quality of life. Conclusions: The intervention could be provided on an individual basis and the trial design was feasible. There were lower attendance rates at group sessions compared to individual sessions.